CsF-Catalyzed Fluoroacylation of Tetrafluoroethylene Using Acyl Fluorides for the Synthesis of Pentafluoroethyl Ketones - Ishida, Naoyoshi; Iwamoto, Hiroaki; Sunagawa, Denise Eimi; Ohashi, Masato; Ogoshi, Sensuke (Synthesis, 2020)
A catalytic method for the synthesis of pentafluoroethyl ketones has been developed. The cesium fluoride catalyst can be used to convert acyl fluorides into the pentafluoroethyl ketones under tetrafluoroethylene pressure without generating stoichiometric quantities of chemical waste. Mechanistic studies suggest that high reaction temperature is crucial for the ketone to be the major product.
Keywords: acyl fluoride; tetrafluoroethylene; pentafluoroethyl ketone; pentafluoroethylation; cesium fluoride; DFT calculations